Pengaruh Struktur Modal, Pertumbuhan Penjualan Dan Ukuran Perusahaan Terhadap Profitabilitas Tiga Perusahaan Ritel Indonesia Yang Terdaftar Di Bursa Efek Indonesia - Ella Fiana; Juli Meliza (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose to analyze the effect of capital structure, sales growth and firm size to theprofitability at three Indonesian retail companies listed of the Indonesia Stock Exchange,partially and simultaneously. Methodology/approach – The sample used in this study amountedthree companies. The study used purposive sampling method and multiple regresion analysisanalysis The data analysis technique used in this research is multiple linear analysis. Findings – The results of the partial test (t test) of the Capital Structure (DER) variable have nopositive and insignificant effect to the Profitability (OPM). Sales Growth has a positive andsignificant effect to the Profitability (OPM). Firm Size has no positive and insignificant effect tothe Profitability (OPM). And simultaneously Capital Structure (DER), Sales Growth and FirmSize have a positive and significant effect to the Profitability (OPM). Novelty/value – The salesgrowth variable is the variable that has the largest partial effect compared to other variables inhe 2018-2021 period (quarterly)